1961
DOI: 10.1136/bmj.1.5234.1205
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Blood-coagulation Factors During Anticoagulant Therapy with Phenindione

Abstract: The complex mechanism of the factors concerned in blood coagulation has been investigated in many ways, not least among these being a study of such factors during anticoagulant therapy, and by the use of plasma from patients treated with anticoagulant drugs in crossmixture experiments with plasma from patients having congenital coagulation defects. Earlier results from such investigations indicated a simple deficiency of prothrombin and "factor VII." It is now known, however, that Christmas factor (Douglas, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1962
1962
1974
1974

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…On the other hand we have found Thrombotest to be a good indicator of deficiency of factor IX ( Fig. 1) in this group of patients, although Thrombotest has been reported as relatively insensitive in detecting deficiency of factor IX in the plasma of patients with Christmas disease or in patients who are receiving therapy with phenindione (Denson, 1961). We do not have an explanation for this (unexpected) finding, although we note that the occasional patient with congenital factor IX deficiency may have a prolonged Thrombotest (Kidd, Denson, and Biggs, 1963).…”
Section: Resultsmentioning
confidence: 50%
“…On the other hand we have found Thrombotest to be a good indicator of deficiency of factor IX ( Fig. 1) in this group of patients, although Thrombotest has been reported as relatively insensitive in detecting deficiency of factor IX in the plasma of patients with Christmas disease or in patients who are receiving therapy with phenindione (Denson, 1961). We do not have an explanation for this (unexpected) finding, although we note that the occasional patient with congenital factor IX deficiency may have a prolonged Thrombotest (Kidd, Denson, and Biggs, 1963).…”
Section: Resultsmentioning
confidence: 50%
“…
The levels of factors I1 (prothrombin), VII, IX and X in the plasma of patients on anticoagulant therapy with phenindione have been shown to be higher by antibody neutralization tests than by specific assays.It has now been established by many authors that the plasma concentrations of prothrombin, factor VII, factor IX and factor X are reduced by anticoagulant therapy with phenindione (Dindevan) (Horder, 1958;Denson, 1961; etc.). Recently it has been shown that structurally defective forms of factors VIII, IX and X can be demonstrated in the plasma of patients with haemophilia, Christmas disease and the factor-X defect (Denson et al, 1968(Denson et al, , 1969(Denson et al, , 1970 Hoyer & Breckenridge, 1969; Hougie& Twomey, 1967).
…”
mentioning
confidence: 99%
“…This supports our clinical impression that the British corrected ratio is a more reliable guide to safe and effective anticoagulation. Denson (1961) showed that when an oral anticoagulant is administered the levels of the various blood clotting factors fall at different rates. Factor VII is the first to fall and this is reflected in a rapidly lengthening prothrombin time.…”
Section: Discussionmentioning
confidence: 99%
“…The test most widely used to control anticoagulant therapy is the one-stage prothrombin time based on Quick's technique (Poller, 1969). This test is sensitive to deficiency of factors II, V, VII, and X but is insensitive to a deficiency of factor IX (Denson, 1961).Haemorrhagic complications may occur when the prothrombin time is within the desired therapeutic range (Pollard et al, 1962), and this is a common clinical observation. Eastham (1968) suggested that the activated partial thromboplastin time was a more valuable test for the control of anticoagulant therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation